2018
DOI: 10.1101/340265
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antiviral viral compound fromStreptomyces ghanaensislike strain against white spot syndrome virus (WSSV) of shrimp

Abstract: 35Actinomycetes isolates collected from different environments were screened for 36 antiviral activity against WSSV. One isolate designated as CAHSH-2 showed antiviral 37 activity against WSSV at the concentration of 0.2 mg per shrimp. The laboratory trial of 38 determining antiviral activity of ethyl acetate extract (EtOAcE) of CAHSH-2 against WSSV 39 was carried out 21 times since 2014. CAHSH-2 isolate which showed antiviral activity was 40 characterized and identified as Streptomyces ghanaensis like strain.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 66 publications
(73 reference statements)
1
14
0
Order By: Relevance
“…In the present study, B. fluminensis gave positive results for starch, casein and gelatin hydrolysis, citrate and urease, while negative results were obtained for methyl-red, Voges–Proskauer and indole tests. Rajkumar et al [ 33 ] isolated actinomycetes from different environments. They reported that the isolated Actinomycetes showed negative Indole, MR and VP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present study, B. fluminensis gave positive results for starch, casein and gelatin hydrolysis, citrate and urease, while negative results were obtained for methyl-red, Voges–Proskauer and indole tests. Rajkumar et al [ 33 ] isolated actinomycetes from different environments. They reported that the isolated Actinomycetes showed negative Indole, MR and VP.…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, we observed that they were able to tolerate up to 7% salt concentration. Rajkumar et al [ 33 ] also reported that the Actinomycetes were able to survive in 9% NaCl. In the present study, equally similar biochemical and physiological characteristics, such as NaCl tolerance (salinity), temperature tolerance, as well as biochemical characteristics of Actinomycetes, were reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The antiviral properties of the methanol extract of the isolates were found to be lesser effective when compared to the whole broth and also these extracts (L27, L35, L45, L56 and B451) showed 40% survival. Another study reported, 64 actinobacterial isolates collected by from different environments, a specific strain designated as CAHSH–2 exhibited potent anti‐WSSV activity at low concentration (0.2 mg) per shrimp (Rajkumar et al., 2018). Antiviral activity of the extracts was tested in marine shrimp, Litopeneaus vannamei infected with WSSV was confirmed by RT‐PCR, Western blot analysis and ELISA.…”
Section: Effects Of Actinobacterial Metabolites Against Wssvmentioning
confidence: 99%